Respuesta :

Answer:

The width is 3x^2

The length is (4x^2+2x+5)


Step-by-step explanation:

12x^4 + 6x^3 + 15x^2


Lets find the greatest common factor

12x^4 = 3*4 x*x*x*x = 3*2*2  x*x*x*x

6x^3 = 3*2 *x*x*x

15x^2 = 5*3*x*x

The common term for each is 3*x*x

The greatest common factor is 3x^2

What is left  after factoring will be the length

12x^4 = 3*4 x*x*x*x = 3*2*2  x*x*x*x  = 3x^2 (2*2*x*x) = 3x^2(4x^2)

6x^3 = 3*2 *x*x*x = (3x^2)(2x)

15x^2 = 5*3*x*x3x^2(5)


12x^4 + 6x^3 + 15x^2 = 3x^2(4x^2+2x+5)

The width is 3x^2

The length is (4x^2+2x+5)